Colored microcrystalline glass as well as preparation method and application thereof
By introducing oxide colorant into the glass components and nucleation, crystallization and ion exchange chemical strengthening, colored microcrystalline glass mainly composed of sodium, the problem of high cost of existing colored glass is solved and the cost is realized Lower and suitable for a variety of applications, colored microcrystalline glass preparation.
Patent Information
- Application Number
- CN202411701338.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-18
AI Technical Summary
Existing non-ferrous glass has high costs and affects signal transmission in applications such as consumer electronic products, and the development of the lithium battery industry has led to an increase in cost of Li.
By introducing oxide colorant into the glass components, a colored microcrystalline glass mainly consists of sodium, with low lithium content and low cost. It also obtains a colored microcrystalline glass through nucleation, crystallization treatment and ion exchange chemical strengthening .
It has realized the preparation of non-colored microcrystalline glass with low cost, suitable for consumer electronic products, display equipment decorative panels, stove stove decorative panels, etc., without affecting signal transmission.
Smart Images

Figure CN119461857A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of microcrystalline glass, and in particular to a colored microcrystalline glass and a preparation method and application thereof. Background Art
[0002] In order to meet consumers' personalized pursuit of different colors for products, non-ferrous metal materials are used to make the back covers of consumer electronic products, decorative panels of various display devices, or decorative panels of stoves and stoves. Or, when transparent materials such as glass or acrylic are used to make products, coating or electroplating spray painting and other processes are used for ink silk screen processing. Although these two methods can achieve various color effects, they also increase the process cost. In addition, the use of non-ferrous metal materials to make the back covers of consumer electronic products will also affect signal transmission.
[0003] Glass-ceramics is a functional material obtained by controlling the crystallization process of basic glass, which contains a large amount of microcrystalline phase and glass phase. This material has excellent mechanical properties, thermal properties and chemical stability, so it has broad application prospects in various industries (including consumer electronics). The above problems can be solved by introducing colored elements (iron, copper, manganese, nickel, selenium, cobalt, chromium, cadmium or rare earth elements) into glass-ceramics, but in the currently disclosed technology, the Li content in the glass formula is relatively high, and the formed crystal form is mainly petalite, lithium silicate, eucryptite, etc. With the development of the lithium battery industry, the corresponding mineral cost for obtaining Li has risen sharply. Therefore, the cost of existing colored glass is still very high and does not have an advantage.
[0004] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0005] Based on the above-mentioned deficiencies of the prior art, the purpose of the present invention is to provide a colored microcrystalline glass and a preparation method and application thereof, aiming to provide a low-cost colored microcrystalline glass to meet the color requirements of materials in different fields.
[0006] The technical solution of the present invention is as follows:
[0007] In a first aspect of the present invention, there is provided a colored glass-ceramic, wherein the colored glass-ceramic comprises the following components in terms of molar percentage:
[0008] SiO2 40%-60%, Al2O3 15%-25%, Na2O 15%-25%, Li2O 1%-5%, K2O0%-3%, MgO 0%-4%, CaO 0%-4%, ZrO2 1%-8%, B2O3 0.5%-8%, P2O5 0.5%-5%, TiO2 0%-3%, clarifier 0.1%-2% and oxide colorant 0.1%-8%;
[0009] Among them, 16%≤Na2O+Li2O+K2O≤30%.
[0010] Optionally, the clarifier includes at least one of SnO2, NaCl and Sb2O3; and / or,
[0011] The oxide colorant includes at least one of CeO2, Fe2O3, NiO, V2O5, Cr2O3, CuO, Er2O3, La2O3, Y2O3, Nd2O3 and Ho2O3.
[0012] Optionally, the crystalline phase of the colored glass-ceramics includes at least one of sodium nepheline, nepheline solid solution, triclinic nepheline, zirconium oxide and β-quartz solid solution.
[0013] Optionally, when the thickness of the colored microcrystalline glass is 0.7 mm, the average transmittance of the colored microcrystalline glass to light within a wavelength range of 380 to 800 nm is 20% to 80%.
[0014] Optionally, the crystallinity of the colored glass-ceramics is greater than or equal to 25% and less than or equal to 80%.
[0015] A second aspect of the present invention provides a method for preparing colored microcrystalline glass, which comprises the following steps:
[0016] The components of the colored glass-ceramics as described above are batched to obtain a mixed material;
[0017] After the mixture is melted, it is molded and annealed to obtain basic glass;
[0018] The colored microcrystalline glass is obtained by sequentially subjecting the basic glass to nucleation treatment and crystallization treatment.
[0019] Optionally, the step of obtaining the colored micro-ceramic glass after sequentially subjecting the base glass to nucleation treatment and crystallization treatment specifically includes:
[0020] The base glass is subjected to nucleation treatment and crystallization treatment in sequence, and then placed in molten salt for ion exchange chemical strengthening to obtain the colored microcrystalline glass.
[0021] Optionally, the mixture is heated at a temperature of 1450 to 1700° C. for 2 to 6 hours to melt;
[0022] The molding method includes a float method, a drawing method, a calendaring method or a casting method;
[0023] The annealing temperature is 300-600° C., and the annealing time is 2-6 hours.
[0024] Optionally, the temperature of the nucleation treatment is 400-600° C., and the time of the nucleation treatment is 2-8 hours;
[0025] The temperature of the crystallization treatment is 540-950° C., and the time of the crystallization treatment is 0.25-3 hours.
[0026] The third aspect of the present invention provides an application of the colored microcrystalline glass as described above or the colored microcrystalline glass prepared by the preparation method as described above in the back cover of consumer electronic products, decorative panels of various display devices or decorative panels of stoves and furnaces.
[0027] Beneficial effects: The present invention adds oxide colorants to the glass components to form colored microcrystalline glass. At the same time, the colored microcrystalline glass is mainly composed of sodium elements, has a low lithium content, and has a low cost. It can be used in the fields of back covers of consumer electronic products, decorative panels of various display devices, and decorative panels of stoves and furnaces. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the XRD diagram of the colored glass in Example 1. DETAILED DESCRIPTION
[0029] The present invention provides a colored microcrystalline glass and a preparation method and application thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0030] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0031] The present invention will be further described below by means of specific examples.
[0032] Some of the terms in this invention are explained as follows:
[0033] Basic glass: glass made by uniformly mixing corresponding compounds of various oxides (including silicon dioxide, aluminum oxide, sodium oxide, calcium oxide, etc.), melting at high temperature and then forming by one of the forming methods including float process, overflow down-draw process, roller pressing process and casting process, and annealing, but without nucleation, crystallization and ion exchange chemical strengthening treatment.
[0034] Glass-ceramics: A type of solid composite material that contains both a glass phase and a crystal phase (microcrystalline phase, crystalline phase) and is prepared by subjecting base glass to a targeted controlled crystallization treatment.
[0035] Nucleation: The base glass is heat treated to make the nucleating material in the glass grow tiny crystal nuclei.
[0036] Crystallization: The base glass is grown into a certain crystal based on the crystal nucleus through heat treatment.
[0037] Crystalline phase: It is the microscopic structure of crystals and is a general term for a large number of crystalline solid phase components.
[0038] Crystallinity: It is used to indicate the proportion of crystals in microcrystalline glass, generally the mass ratio of the crystalline phase to the entire microcrystalline glass.
[0039] Glass phase: It is an amorphous mineral phase with low refractoriness. It is in glass phase at room temperature, gradually softens during heating, and finally becomes liquid phase. The glass phase alone or together with some crystalline minerals fills the main crystal phase to form the material matrix, also known as the binding phase.
[0040] Transmittance: The ratio of the radiant energy that is projected and passes through an object to the total radiant energy that is projected onto the object during the process of the incident light flux leaving from the illuminated surface or the incident surface of the medium to the other side.
[0041] Lab value: Lab is a color model based on physiological characteristics, where L represents brightness, a includes colors from dark green to gray to bright pink, and b includes colors from bright blue to gray to yellow.
[0042] An embodiment of the present invention provides a colored glass-ceramic, wherein the colored glass-ceramic includes the following components in terms of molar percentage:
[0043] SiO2 40%-60%, Al2O3 15%-25%, Na2O 15%-25%, Li2O 1%-5%, K2O0%-3%, MgO 0%-4%, CaO 0%-4%, ZrO2 1%-8%, B2O3 0.5%-8%, P2O5 0.5%-5%, TiO2 0%-3%, clarifier 0.1%-2% and oxide colorant 0.1%-8%;
[0044] Among them, 16%≤Na2O+Li2O+K2O≤30%, and the sum of the molar percentages of each component is 100%.
[0045] In an embodiment of the present invention, an oxide colorant is added to the glass component to form a colored microcrystalline glass. At the same time, the colored microcrystalline glass is mainly composed of sodium element (sodium element can form sodium nepheline or triclinic nepheline), has a low lithium content, and has a low cost. It can be applied to the back covers of consumer electronic products, decorative panels of various display devices, and decorative panels of stoves and furnaces.
[0046] In the embodiment of the present invention, the colored glass-ceramics may have the following range of transmission color coordinates in the Lab color space: L*=15~95; a*=-60~60; b*=-60~60. Further, the colored glass-ceramics may have the following range of transmission color coordinates in the Lab color space: L*=30~90; a*=-40~50; b*=0~50.
[0047] The colored microcrystalline glass is absorptive in the visible light range. The colored microcrystalline glass with a thickness of 0.7 mm has an average light transmittance of 20% to 80% for light in the wavelength range of 380 to 800 nm.
[0048] In this embodiment, SiO2 is introduced into the components of the colored glass-ceramics, and SiO2 is the component with the highest content. As the main network former, SiO2 can stabilize the network structure, constitute the main structure of the precursor and the colored glass-ceramics, and is also the main component of some crystalline phases. Too low SiO2 content will weaken the overall performance of the colored glass-ceramics, and the molar content of SiO2 should not be less than 40%; too high SiO2 content will lead to difficulties in melt molding, and the component contains a high silicon component, which further increases the difficulty of melting the colored glass-ceramics precursor. Therefore, taking all factors into consideration, the present embodiment is with SiO The molar content is controlled between 40% and 60%, for example SiO The molar content is 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60% or any value in the numerical range composed of any two numerical values in the above-mentioned numerical value as endpoints. Specifically, SiO The molar content is 44% to 59%.
[0049] Al2O3 is an intermediate oxide formed by colored microcrystalline glass, and is also the main component of sodium nepheline, triclinic nepheline and other crystal forms. It can significantly improve the thermal stability of basic glass and colored microcrystalline glass. At the same time, since [AlO4] is larger than [SiO4] in volume, it can provide more space for ion exchange, so Al2O3 can promote ion exchange. However, too high Al2O3 content will increase the viscosity of the basic glass, which is not conducive to melting. Considering comprehensively, the molar content of Al2O3 is 15% to 25%, for example, the molar content of Al2O3 is 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25% or any value in the numerical range composed of any two of the above values as endpoints. Specifically, the molar content of Al2O3 is 16% to 23%.
[0050] Na2O is one of the main components of sodium nepheline and triclinic nepheline, and is also an important element in the subsequent chemical strengthening process. At the same time, Na2O is a flux when the base glass is melted at high temperature, which can significantly reduce the melting temperature of the base glass. However, when the Na2O content is higher than 25%, the chemical stability of the colored microcrystalline glass will be significantly reduced. Therefore, the ideal molar content of Na2O should be less than or equal to 25%, which can not only keep the melting temperature within a suitable range, but also ensure good ion exchange properties. Taking all factors into consideration, the molar content of Na2O is 15% to 25%, for example, the molar content of Na2O is 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25% or any value in the numerical range composed of any two of the above values as endpoints. Specifically, the molar content of Na2O is 15% to 23%.
[0051] Li2O is an oxide with high alkali metal activity and is an external oxide of the glass network. As one of the additives to reduce the high temperature viscosity of the base glass, it can significantly improve the high temperature fluidity of the glass. + In colored microcrystalline glass, it can participate in ion exchange chemical strengthening reaction to further enhance the mechanical properties of colored microcrystalline glass. In the present invention, the Li element does not participate in crystallization, but can be used for secondary chemical strengthening of glass to further improve its mechanical properties. Taking all factors into consideration, the molar content of Li2O is 1% to 5%, for example, the molar content of Li2O is 1%, 2%, 3%, 4%, 5% or any value in the numerical range consisting of any two of the above values as endpoints.
[0052] K2O is an optional component for improving the low temperature melting property and formability of glass, but if the molar content of K2O is too high, it is easy to reduce the chemical stability of glass. Taking all factors into consideration, the molar content of K2O is 0% to 3%, for example, the molar content of K2O is 0%, 1%, 2%, 3% or any value in the numerical range consisting of any two of the above numerical values as endpoints.
[0053] Taking all factors into consideration, the total molar content of Na2O, Li2O and K2O is 16% to 30%, for example, the total molar content of Na2O, Li2O and K2O is 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30% or any value in a numerical range consisting of any two of the above numerical values as endpoints.
[0054] MgO can improve the melting of base glass, lower the liquidus temperature, and help improve the thermal stability of colored glass-ceramics. At the same time, MgO can improve the chemical stability and mechanical strength of colored glass-ceramics, and can reduce the crystallization tendency of colored glass-ceramics. However, when its content is too high, the crystallization performance of colored glass-ceramics is reduced, which is not conducive to the colored glass-ceramics obtaining the desired crystal phase type and grain size. Therefore, the molar content of MgO in the glass-ceramics component is 0% to 4%, for example, it can be 0%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4% or any value in the numerical range composed of any two of the above values as endpoints. Specifically, the molar content of MgO is 0% to 2%.
[0055] CaO, as a network exo-oxide formed by colored glass-ceramics, helps to reduce the viscosity of colored glass-ceramics, inhibits the crystallization of colored glass-ceramics during the molding of colored glass-ceramics, and can also improve the low-temperature melting property of colored glass-ceramics. However, excessive CaO will reduce the devitrification resistance of colored glass-ceramics. By adding an appropriate amount of CaO, the viscosity of colored glass-ceramics can be reduced without affecting the crystallization performance of colored glass-ceramics. Taking all factors into consideration, the molar content of CaO is 0% to 4%, for example, the molar content of CaO is 0%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4% and any one of the ranges consisting of any two of the above values. Specifically, the molar content of CaO is 0.2% to 2%.
[0056] ZrO2 is an intermediate oxide formed by colored microcrystalline glass, which can improve the chemical stability of colored microcrystalline glass, increase the hardness of colored microcrystalline glass, and increase the ability of colored microcrystalline glass to resist scratches and drops. At the same time, due to the high cationic charge and strong field of ZrO2, it has a greater accumulation effect on the structure of colored microcrystalline glass, and is used as a nucleating agent in colored microcrystalline glass. However, excessive ZrO2 will significantly increase the viscosity of colored microcrystalline glass and affect the molding ability of colored microcrystalline glass. Taking all factors into consideration, the molar content of ZrO2 is 1% to 8%, for example, the molar content of ZrO2 is 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8% or any value in the numerical range composed of any two of the above values as endpoints.
[0057] B2O3, as a network exosome oxide of colored glass-ceramics, is generally filled in the voids of the silicon-oxygen tetrahedral framework, and its cation coordination rarely changes, and some properties of its oxide can be considered constant. B2O3 helps to provide a base glass with a low melting temperature. In addition, the addition of B2O3 can also improve the damage resistance of colored glass-ceramics. Taking all factors into consideration, the molar content of B2O3 is 0.5% to 8%, for example, the molar content of B2O3 is 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8% or any value in the numerical range composed of any two of the above values as endpoints. Specifically, the molar content of B2O3 is 0.5% to 7%.
[0058] P2O5 is used as a nucleating agent to promote the phase separation and overall crystallization ability of the base glass. If the P2O5 content is too low, the base glass does not crystallize, and only forms crystals from the surface to the inside at a higher temperature and low viscosity; if the P2O5 content is too high, it will be difficult to control devitrification when cooling during the formation of the base glass. Taking all factors into consideration, the molar content of P2O5 is 0.5% to 5%, for example, the molar content of P2O5 is 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or any value in the numerical range consisting of any two of the above numerical values as endpoints.
[0059] TiO2 is one of the nucleating agents for the nucleation and growth of crystals in microcrystalline glass, which can effectively promote the growth of crystal nuclei in the process of nucleation and crystallization of the base glass, and at the same time improve the stability of the glass; the introduction of TiO2 effectively promotes the precipitation of crystal nuclei in the nucleation process, and at the same time, the introduction of TiO2 easily causes the base glass to undergo phase separation, leading to crystallization, and affecting the formation of the glass. Taking all factors into consideration, the molar content of TiO2 is 0% to 3%, for example, the molar content of TiO2 is 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, or any value in the numerical range consisting of any two of the above numerical values as endpoints.
[0060] In some embodiments, the clarifier includes at least one of SnO2, NaCl and Sb2O3. SnO2, NaCl and Sb2O3 are good clarifiers in the production of colored microcrystalline glass, which can effectively homogenize the components of the precursor glass and reduce the formation of undesirable substances such as bubbles and stones. Taking all factors into consideration, the total molar content of one or more of SnO2, NaCl and Sb2O3 is 0.1% to 2%, for example, the molar content of one or more of the three is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% or any value in the numerical range composed of any two of the above values as endpoints. Specifically, it is 0.5% to 2%.
[0061] In some embodiments, the oxide colorant includes at least one of CeO2, Fe2O3, NiO, V2O5, Cr2O3, CuO, Er2O3, La2O3, Y2O3, Nd2O3 and Ho2O3. Taking all factors into consideration, the molar content of the oxide colorant is 0.1% to 8%, for example, the molar content of the oxide colorant is 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8% or any value in the numerical range consisting of any two of the above numerical values as endpoints.
[0062] In some embodiments, the crystalline phase of the colored glass-ceramics includes at least one of sodium nepheline, nepheline solid solution, triclinic nepheline, zirconia, and β-quartz solid solution.
[0063] In some embodiments, the crystallinity of the colored glass-ceramics is greater than or equal to 25% and less than or equal to 80%.
[0064] The present invention also provides a method for preparing colored glass-ceramics, which comprises the following steps:
[0065] S1. Mixing the components of the colored glass-ceramics according to the present invention to obtain a mixture;
[0066] S2, melting the mixed material, molding and annealing to obtain basic glass;
[0067] S3. The basic glass is subjected to a nucleation treatment and a crystallization treatment in sequence to obtain the colored microcrystalline glass.
[0068] The preparation method provided by the present invention is simple, and an oxide colorant is added to the components to form a colored microcrystalline glass. At the same time, the colored microcrystalline glass is mainly composed of sodium element (sodium element forms sodium nepheline and triclinic nepheline), has a low lithium content, and has a low cost. It can be applied to the back covers of consumer electronic products, decorative panels of various display devices, and decorative panels of stoves and furnaces.
[0069] In step S2, in some embodiments, the mixture is heated at a temperature of 1450-1700°C (for example, 1450°C, 1500°C, 1550°C, 1600°C, 1650°C, 1700°C or any value in a numerical range consisting of any two of the above values as endpoints) for 2-6h (for example, 2h, 3h, 4h, 5h, 6h or any value in a numerical range consisting of any two of the above values as endpoints) to melt.
[0070] In some embodiments, the forming method includes a float method, a drawing method, a calendaring method or a casting method, but is not limited thereto.
[0071] In some embodiments, the annealing temperature is 300-600°C (for example, it can be 300°C, 320°C, 340°C, 360°C, 380°C, 400°C, 420°C, 440°C, 460°C, 480°C, 500°C, 520°C, 540°C, 560°C, 580°C, 600°C or any value in a numerical range consisting of any two of the above values as endpoints), and the annealing time is 2-6h (for example, it can be 2h, 3h, 4h, 5h, 6h or any value in a numerical range consisting of any two of the above values as endpoints).
[0072] In step S3, in some embodiments, the temperature of the nucleation treatment is 400-600°C (for example, it can be 400°C, 420°C, 440°C, 460°C, 480°C, 500°C, 520°C, 540°C, 560°C, 580°C, 600°C or any value in a numerical range consisting of any two of the above values as endpoints), and the time of the nucleation treatment is 2-8h (for example, it can be 2h, 3h, 4h, 5h, 6h, 7h, 8h or any value in a numerical range consisting of any two of the above values as endpoints).
[0073] In some embodiments, the temperature of the crystallization treatment is 540-950°C (for example, it can be 540°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C or any value in a numerical range consisting of any two of the above values as endpoints), and the time of the crystallization treatment is 0.25-3h (for example, it can be 0.25h, 0.5h, 1.0h, 1.5h, 2.0h, 2.5h, 3.0h or any value in a numerical range consisting of any two of the above values as endpoints).
[0074] In the process of preparing colored glass-ceramics, it is necessary to strictly control the temperature and time of the heat treatment step, thereby controlling the type, size and proportion of precipitated crystals, which can also affect the final integrity, quality, color and / or opacity of the obtained colored glass-ceramics. In some embodiments, the crystalline phase of the colored glass-ceramics prepared by the preparation method includes at least one of sodium nepheline, nepheline solid solution, triclinic nepheline, zirconium oxide and beta quartz solid solution, and the crystallinity is in the range of 25% to 80%.
[0075] In step S3, in some embodiments, the steps of sequentially subjecting the base glass to nucleation treatment and crystallization treatment to obtain the colored micro-ceramic glass specifically include:
[0076] The base glass is subjected to nucleation treatment and crystallization treatment in sequence, and then placed in molten salt for ion exchange chemical strengthening to obtain the colored microcrystalline glass (i.e. the strengthened colored microcrystalline glass, which can also be called chemically strengthened colored microcrystalline glass).
[0077] The present invention also provides an application of the colored microcrystalline glass as described above in the embodiment of the present invention or the colored microcrystalline glass prepared by the preparation method described above in the embodiment of the present invention in the back cover of consumer electronic products, decorative panels of various display devices or decorative panels of stoves and furnaces.
[0078] The colored microcrystalline glass provided by the embodiments of the present invention can be used in various applications, for example, cover glass or glass back panels in consumer or commercial electronic devices (such as LCD and LED displays, computer monitors, ATMs, televisions and cameras), touch screens or touch sensors, portable electronic devices (such as mobile phones, personal media players and tablets), integrated circuits (such as semiconductor chips), photovoltaics (such as architectural glass), vehicle (such as automobile) glass, and commercial or household appliances.
[0079] As an example, the colored glass-ceramics is applied to consumer electronic devices, which include:
[0080] shell;
[0081] an electronic assembly at least partially or completely located within the housing and including at least a controller, a memory, and a display located on or adjacent to a front surface of the housing;
[0082] and a cover substrate located on or above the front surface of the housing so that it is located above the display;
[0083] Wherein, at least a portion of at least one of the covering substrate and / or the outer shell may include the colored micro-ceramic glass.
[0084] The present invention will be further described below by means of specific examples.
[0085] Table 1. Formula of glass in various embodiments and comparative examples
[0086]
[0087] Example 1
[0088] This embodiment provides a method for preparing colored microcrystalline glass, comprising the following steps:
[0089] (1) According to the components and proportions in Example 1 in Table 1, weigh the raw material powders, and then place them in a mixer and mix them for 30 minutes to obtain a mixture;
[0090] (2) The mixture is transferred to a platinum crucible, melted at 1600°C for 3 hours, poured into a molding mold, and after a casting process, annealed at 420°C for 2 hours. After cooling, a basic glass is obtained.
[0091] (3) The above-mentioned base glass is placed in an annealing furnace and kept at 513°C for 180 minutes for nucleation treatment, then heated to 590°C and kept at this temperature for 20 minutes for crystallization treatment, then cooled to room temperature with the furnace, and then ion exchanged in a molten salt (99wt% NaNO3+1wt% KNO3) at 460°C for 8 hours for chemical strengthening to obtain colored microcrystalline glass.
[0092] Example 2
[0093] This embodiment provides a method for preparing colored microcrystalline glass, which is different from Embodiment 1 only in that: weighing each raw material powder according to the components and proportions in Embodiment 2 in Table 1;
[0094] In step (3), the temperature is kept at 531°C for 300 minutes for nucleation treatment, and then the temperature is increased to 613°C and kept for 40 minutes for crystallization treatment.
[0095] Example 3
[0096] This embodiment provides a method for preparing colored microcrystalline glass, which is different from Embodiment 1 only in that: weighing the raw material powders according to the components and proportions in Embodiment 3 in Table 1;
[0097] In step (3), the temperature is kept at 563°C for 360 minutes for nucleation treatment, and then the temperature is increased to 681°C and kept at this temperature for 30 minutes for crystallization treatment.
[0098] Example 4
[0099] This embodiment provides a method for preparing colored microcrystalline glass, which is different from Embodiment 1 only in that: weighing the raw material powders according to the components and proportions in Embodiment 4 in Table 1;
[0100] In step (3), the temperature is kept at 515°C for 240 minutes for nucleation treatment, and then the temperature is increased to 601°C and kept for 60 minutes for crystallization treatment.
[0101] Example 5
[0102] This embodiment provides a method for preparing colored microcrystalline glass, which is different from Embodiment 1 only in that: weighing the raw material powders according to the components and proportions in Embodiment 5 in Table 1;
[0103] In step (3), the temperature is kept at 533°C for 240 minutes for nucleation treatment, and then the temperature is increased to 640°C and kept for 30 minutes for crystallization treatment.
[0104] Example 6
[0105] This embodiment provides a method for preparing colored microcrystalline glass, which is different from Embodiment 1 only in that: weighing the raw material powders according to the components and proportions in Embodiment 6 in Table 1;
[0106] In step (3), the temperature is kept at 588°C for 360 minutes for nucleation treatment, and then the temperature is increased to 670°C and kept for 15 minutes for crystallization treatment.
[0107] Comparative Example 1
[0108] This comparative example provides a method for preparing glass-ceramics, which is different from Example 1 only in that: weighing the raw material powders according to the components and proportions in Comparative Example 1 in Table 1;
[0109] In step (3), the temperature is kept at 533°C for 240 minutes for nucleation treatment, and then the temperature is increased to 640°C and kept for 30 minutes for crystallization treatment.
[0110] Comparative Example 2
[0111] This comparative example provides a method for preparing a chemically strengthened glass-ceramics, which is different from Example 1 only in that: weighing the raw material powders according to the components and proportions in Comparative Example 2 in Table 1;
[0112] In step (3), the temperature is kept at 523°C for 240 minutes for nucleation treatment, and then the temperature is increased to 619°C and kept for 60 minutes for crystallization treatment.
[0113] test:
[0114] 1. Crystal form and crystallinity test:
[0115] The glass-ceramics were ground into powder and subjected to Rigaku Smartlab X-ray diffraction (XRD) test, and the crystal phase composition and crystallinity were analyzed using Jade.
[0116] 2. L value, a value and b value test in Lab:
[0117] The L value, a value and b value of the glass in each example were tested using a colorimeter (model CM-3600A).
[0118] 3. Average transmittance test:
[0119] The average transmittance of a glass sample with a thickness of 0.7 mm in the 380-800 nm light band was tested using a Shimadzu UV-visible spectrophotometer UV-2600.
[0120] 4. Vickers hardness test:
[0121] The Vickers hardness of the microcrystalline glass was tested using a digital display small load Vickers hardness tester VTD405 (Beijing Wowei Technology Co., Ltd.) in accordance with the national standard GB / T37900-2019 "Ultra-thin glass hardness and fracture toughness test method small load Vickers hardness indentation method". When the present invention performs the Vickers hardness test, the glass sample with a length, width and thickness of 50mm×50mm×0.7mm is tested.
[0122] 5. Impact strength test:
[0123] Average sandpaper drop height: refers to the ratio of the sum of the sandpaper drop heights of each sample measured in multiple identical glass samples to the number of glass samples, which is used to characterize the drop resistance of glass. Take at least 10 identical glass samples for testing each time to obtain the average sandpaper drop height.
[0124] The test method for the sandpaper drop resistance of each glass sample is as follows:
[0125] Step 1: Paste 120-grit sandpaper on the lower surface of the 160g model machine and place the model machine on the green figure LT-SKDL-CD drop machine.
[0126] Step 2: Place a glass sample to be tested with a length, width and thickness of 50mm×50mm×0.7mm directly below the model machine, with the glass sample facing the sandpaper. Make the model machine fall from a certain drop height to impact the glass sample directly below the model machine. If the glass sample does not break, the drop height of the model machine is increased according to a certain rule. For example, the drop height starts from 40cm, and the glass sample is dropped once. If it does not break, increase the height by 10cm each time and drop again until the glass sample breaks.
[0127] Step 3: The last drop height of the glass sample when it breaks is recorded as the anti-sandpaper drop height. For example, if the drop height when it breaks is 100 cm, the anti-sandpaper drop height of the sample is 90 cm.
[0128] The above measured results are as follows Figure 1 And as shown in Table 2.
[0129] Table 2. Test results of embodiments and comparative examples
[0130]
[0131]
[0132] From the above results, it can be seen that the embodiments of the present invention can prepare colored glass-ceramics of different colors, and each colored glass-ceramics has a high Vickers hardness and impact strength. However, from Comparative Example 2, when Li2O is not added, although colored glass-ceramics (such as light green glass-ceramics) can still be prepared, the mechanical properties of the prepared colored glass-ceramics are significantly reduced.
[0133] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A colored glass-ceramic, characterized in that: The colored glass-ceramics comprises the following components in terms of molar percentage: SiO2 40%-60%, Al2O3 15%-25%, Na2O 15%-25%, Li2O 1%-5%, K2O 0%-3%, MgO 0%-4%, CaO 0%-4%, ZrO2 1%-8%, B2O3 0.5%-8%, P2O5 0.5%-5%, TiO2 0%-3%, clarifier 0.1%-2% and oxide colorant 0.1%-8%; Among them, 16%≤Na2O+Li2O+K2O≤30%.
2. The colored glass-ceramics according to claim 1, characterized in that: The clarifier includes at least one of SnO2, NaCl and Sb2O3; and / or, The oxide colorant includes at least one of CeO2, Fe2O3, NiO, V2O5, Cr2O3, CuO, Er2O3, La2O3, Y2O3, Nd2O3 and Ho2O3.
3. The colored glass-ceramics according to claim 1, characterized in that: The crystalline phase of the colored microcrystalline glass includes at least one of sodium nepheline, nepheline solid solution, triclinic nepheline, zirconium oxide and beta quartz solid solution.
4. The colored glass-ceramics according to claim 1, characterized in that: The crystallinity of the colored microcrystalline glass is greater than or equal to 25% and less than or equal to 80%.
5. The colored glass-ceramics according to claim 1, characterized in that: When the thickness of the colored microcrystalline glass is 0.7 mm, the average transmittance of the colored microcrystalline glass to light within a wavelength range of 380 to 800 nm is 20% to 80%.
6. A method for preparing colored microcrystalline glass, characterized in that: The steps include: Mixing the components of the colored glass-ceramics according to claim 1 to obtain a mixed material; After the mixture is melted, it is molded and annealed to obtain basic glass; The colored microcrystalline glass is obtained by sequentially subjecting the basic glass to nucleation treatment and crystallization treatment.
7. The preparation method according to claim 6, characterized in that: The steps of sequentially subjecting the base glass to nucleation treatment and crystallization treatment to obtain the colored micro-ceramic glass specifically include: The base glass is subjected to nucleation treatment and crystallization treatment in sequence, and then placed in molten salt for ion exchange chemical strengthening to obtain the colored microcrystalline glass.
8. The preparation method according to claim 6, characterized in that: The mixed material is heated at a temperature of 1450 to 1700° C. for 2 to 6 hours to melt; The molding method includes a float method, a drawing method, a calendaring method or a casting method; The annealing temperature is 300-600° C., and the annealing time is 2-6 hours.
9. The preparation method according to claim 6, characterized in that: The temperature of the nucleation treatment is 400-600°C, and the time of the nucleation treatment is 2-8h; The temperature of the crystallization treatment is 540-950° C., and the time of the crystallization treatment is 0.25-3 hours.
10. Use of the colored microcrystalline glass described in any one of claims 1 to 5 or the colored microcrystalline glass prepared by the preparation method described in any one of claims 6 to 9 in the back cover of consumer electronic products, decorative panels of various display devices or decorative panels of stoves and furnaces.